Odpowiedź:
[tex]\huge\boxed{d) \ -2t+s-2,5}[/tex]
[tex]\huge\boxed{e) \ -17x+5y}[/tex]
[tex]\huge\boxed{f) \ 4g+2,2}[/tex]
Szczegółowe wyjaśnienie:
Podpunkt d)
[tex]\frac{4t-8}{4}+(-6t+2s-1):2=\frac{\not4(t-2)}{\not4}+(-6t:2+2s:2-1:2)=\\\\=t-2+(-3t+s-0,5)=t-2-3t+s-0,5=-2t+s-2,5[/tex]
Podpunkt e)
[tex]-6x-(3x-y)+4(-2x+y)=-6x-3x+y-8x+4y=\\\\=-6x-3x-8x+y+4y=-17x+5y[/tex]
Podpunkt f)
[tex]\frac{12g+4}{2}-\frac{10g-1}{5}=\frac{\not2(6g+2)}{\not2}-\frac{\not5(2g-0,2)}{\not5}=6g+2-(2g-0,2)=\\\\=6g+2-2g+0,2=6g-2g+2+0,2=4g+2,2[/tex]